If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + 5m) = -54 (2 * 3 + 5m * 3) = -54 (6 + 15m) = -54 Solving 6 + 15m = -54 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 15m = -54 + -6 Combine like terms: 6 + -6 = 0 0 + 15m = -54 + -6 15m = -54 + -6 Combine like terms: -54 + -6 = -60 15m = -60 Divide each side by '15'. m = -4 Simplifying m = -4
| 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 | | 9+3b=15 | | 75.36=2r*3.14 | | 5m=10-5m | | 3(x+15)+4(9-x)=0 | | 8r=-4r-12 | | x^2-6=55 | | 0.2x+9=8(0.4x-1) | | -2=3n+6-5n | | 244.92=2r*3.14 | | -3+2x=3x-4 | | 9(3x-1)-5=6x | | 8x-5=-2x+1 | | 2+3x=6+4x | | -.01t^2+.7t-10=0 | | 8x-5=-2x+11 | | 6(y-2)=-36 | | 200.96=3.14*r^2 | | 6a+3(a+4)=-15 |